ANALYSIS OF TOURISM POTENTIAL STAVROPOL REGION - Margarita Stepanenko (Вестник Северо-Кавказского федерального университета, 2022)
TOURISM POTENTIAL STAVROPOL REGION The article is dedicated to the development matters of tourist potential in the Stavropol region. The author analyzed the strong and weak sides of the tourist development branch and factors, which promote an increase of tourist attraction ofthe region. Recommended activities aimed at the development of tourism in the Stavropol region.